Shared Land/Conflicting Identity: Trajectories of Israeli and Palestinian Symbol Use - Rowland, Robert C. (Rhetoric and Public Affairs, 2002)
Intro -- Contents -- Introduction -- Key Exigencies in the Israeli-Palestinian Conflict -- Chapter 1: The Symbolic Roots of the Israeli-Palestinian Conflict -- Chapter 2: A Symbolic Template for Analyzing the Israeli-Palestinian Conflict -- Chapter 3: The Birth of the Symbolic Systems of Labor and Revisionist Zionism -- Chapter 4: The Symbolic Construction of the Palestinian People -- Chapter 5: Symbolic Trajectories in the Development of Labor and Revisionist Zionism -- Chapter 6: The Essential Palestinian -- Chapter 7: From Camp David to Lebanon -- Chapter 8: From the Occupation to Intifada -- Chapter 9: Symbolic Stagnation and Ideological Calcification in Israel -- Chapter 10: Palestinian Symbolic Trajectories to Oslo -- Chapter 11: Palestinian Myth and the Reality of Oslo -- Chapter 12: From Symbolic Stasis to the End of Revisionism -- Chapter 13: Symbol Use and the Israeli-Palestinian Conflict -- Notes -- Selected Bibliography -- Index.